Curriculum Development for Early Childhood Education Based on Greening Adaptation for Coastal Environmental Resilience: A CaseStudy of Rob Disaster in Tirto Subdistrict - Fadhilah, Fadhilah; Waluyo, Edi; Formen, Ali (Program Studi Magister Pendidikan Anak Usia Dini, 2026)
This research and development (R&D) aims to produce and validate an early childhood education curriculum based on adaptation to greening for meaningful and effective coastal environmental resilience in instilling values of environmental awareness and disaster preparedness from an early age. Product validation, conducted by subject matter experts and early childhood education teachers, showed very feasible results with high scores for content validity (96%), design and components (93.33%), and feasibility (95%). These results indicate that the developed curriculum is valid, practical, and ready for implementation. This curriculum serves as a valuable educational tool for teachers and principals, helping them create learning processes that are relevant to the daily lives of children in coastal areas.Although this study proves the effectiveness of the curriculum as a valid and feasible medium of information, the limitations of the short implementation period restrict the observation of long-term impacts. Therefore, further research is recommended to be conducted over a longer period, with a wider geographical coverage, and considering activities such as class outings to evaluate the sustainable impact. Collaboration with relevant parties is also recommended to improve the scalability of this curriculum.